PROGRAM KKN UNIVERSITAS MATARAM PADA WISATA DANAU DI DESA TUA DI UJUNG UTARA LOMBOK TIMUR: PROGRAM KKN UNIVERSITAS MATARAM PADA WISATA DANAU DI DESA TUA DI UJUNG UTARA LOMBOK TIMUR - Yadnya, Made Sutha; Nurhasanah; Kurniadianto, Dwi; Hajatsyah, Lani Sapitri; Wulandari, Zurrizka Putri; Azminda, Muhammad Azwar Fidar; Kurniawan, Aldhi Putra Ade; Rahayuningsih, Ramdani; Atsani, Affan (Jurnal Wicara, 2024)
Tourism is everything related to tourism including the business of tourist objects and attractions and related businesses in the field. Many places in West Nusa Tenggara Province have great potential for tourists to visit. One of the tourist spot located at the northern end of East Lombok is in the old village of Obel-Obel. This village has a tour "Lake Gumbang Ganang" which is famous for its uniqueness and beauty. Gumbang Ganang Lake is sourced from springs which flows directly from the mountains Through social media created by KKN Unram, PMD 2023 helps promote this tourist spot and hopes that those who see it are interested in visiting this Gumbang Ganang tourist spot. The Bale Lokaq traditional house is one of the traditional houses with a unique architectural form typical of Lombok and still survives to this day. Full of philosophical meaning, the Bale traditional house is proof of the high philosophy of life of the Lombok people, especially the Sasak tribe. The people of Lombok have bale lokak houses that are more than just a place to live. In this building there are various hopes and traditional values ​​that are upheld. These traditional values ​​are presented through the architectural design and contraction of the typical Lombok bale traditional house